Key Financial Determinants in Reducing Financial Distress in Indonesia’s Manufacturing Industry - Silalahi, Harlen; Sitompul, Ganda Tua; Silalahi, Dumariani; Siregar, Zulkheiri Surya Putra; Nababan, Megawati (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study investigates key financial factors that influence the reduction of financial distress among manufacturing firms in Indonesia. Motivated by the limited literature on proactive financial strategies, the research focuses on four main financial indicators: profitability (ROA), liquidity (CR), leverage (DAR), and sales growth. Using a sample of 27 manufacturing companies listed on the Indonesia Stock Exchange over a five-year period (2018–2022), this study analyzes 135 firm-year observations. Financial distress is measured using the year-on-year change in the Altman Z-Score. Employing multiple linear regression, the findings reveal that profitability and liquidity significantly and positively affect the reduction of financial distress. In contrast, leverage and sales growth show no significant impact. The study also observes a general declining trend in financial distress across the sector during the observation period. These results highlight the importance of effective asset management and liquidity planning in maintaining financial stability. Practical recommendations include optimizing asset utilization, reducing reliance on short-term debt, and enhancing working capital efficiency to mitigate financial distress risks. Keywords: Profitability, Liquidity, Financial Distress, Manufacturing Industry, Financial Stability